Os mestrados profissionais do Ifal e seus produtos educacionais e técnico- tecnológicos: a verticalização do ensino e a pesquisa enquanto princípio pedagógico (2018-2023) - Silva, Adriana Rodrigues de Oliveira da (2025)
This research was developed within the scope of the Postgraduate Program in Professional and Technological Education - PROFEPT and aimed to develop an educational product called: Catalog of Educational and Technological Products of the Professional Masters of IFAL (2018-2023). The present study sought to examine the production of the professional masters degrees of the Federal Institute of Alagoas, PROFEPT, Professional Masters in Professional and Technological Education and PPGTEC, Masters in Environmental Technologies. It was observed that these postgraduate programs have in common the challenge of developing products that culminate in objective responses to the problems posed in the themes of education and the environment, respectively. The theoretical interlocutions were carried out based on authors who deal with professional and technological education, such as (Barbier, 2007), (Bomfim, 2018), (Ciavatta, 2014), (Frigotto, Ciavatta, Ramos, 2012), (Freire, 1999), (Ibiapina, 2008), (Pimenta, 2007), (Pio, 2012), (Quevedo, 2018), (Tardif, 2019), whose methodology is based on studies by (Martins, 2004), (Backes, 2011), (Silva, 2013). In methodological terms, the study was investigative, qualitative, of the action research type, whose methodological instruments for data collection included the application of a questionnaire and bibliographic research. The qualitative method used consisted of research, reading of the Federal Constitution of 1988, the Law of Guidelines and Bases of Education, analysis of the standards, plans, regulations, annex of the regulation, institutional development plan, rules, resolutions of the aforementioned postgraduate programs; assessment of the training of the teaching staff and the production of professional master's degrees; investigation of the official website and repository of dissertations and products developed. The result of the research demonstrated the relevance of educational products for education and the importance of technical-technological products for science. Based on the results, an educational product was prepared in the format of a Catalog of Educational and Technological Products of the Professional Master's Degrees of IFAL, a proposal that observed the productions of the two stricto sensu postgraduate programs of IFAL - PROFEPT and PPGTEC. The (PE) prepared may contribute to the recognition of IFAL as a research institution with the consequent positive impact. Still in relation to the results of this investigation, it is possible to historicize the trajectory of IFAL's stricto sensu postgraduate programs since their implementation and systematize the products available in their repositories in order to measure the importance of these programs to promote the development and transfer of technologies at the state level. From the collection and interpretation, it was possible to establish some considerations about the professional master's degrees, as well as the educational and technological products. The number of educational products (58) between (2020-2023) of PROFEPT. The number of products (86) between (2019-2023) of PPGTEC. Therefore, it is possible to envision the possibility of this work and the (PE) Catalog of Educational and Technological Products of IFAL's Professional Master's Degrees contributing to the promotion of science, technology, culture and work in the Federal Education Network, as well as to society.